Impacts of different vegetation restoration options on gully head soil resistance and soil erosion in loess tablelands. Issue 4 (23rd January 2020) - Guo, Mingming; Wang, Wenlong; Wang, Tianchao; Wang, Wenxin; Kang, Hongliang
Abstract: Vegetation restoration is identified as an effective approach to control soil erosion and affects soil detachment and resistance to concentrated flow on the Loess Plateau. However, the effects of vegetation restoration at gully heads in loess‐tableland remains unclear. This study was performed to investigate the effects of nine vegetation restoration types at gully heads on soil detachment rate (Dr) and soil resistance to concentrated flow (i.e. soil erodibility, K r and critical shear stress, τ c ). Undisturbed soil samples were collected from nine vegetation‐restored lands and one slope cropland (as the control) and were subjected to a hydraulic flume to obtain Dr values of gully heads under six inflow discharges (0.5–3.5 L s ‐1 ). The results showed that the Dr values of nine revegetated gully heads were 77.11% to 95.81% less than that of slope cropland, and the grassland dominated by Cleistogenes caespitosa and the shrubland dominated by Hippophae rhamnoides had a relatively greater decrease in Dr than those of other seven restoration types. The Dr value of nine revegetated gully heads could be better simulated by stream power than by flow velocity and shear stress and was also significantly affected by soil disintegration rate (positively), soil bulk density, saturated hydraulic conductivity, organic matter content, and water‐stable aggregate stability (negatively). Additionally, roots with diameters of 0 to 0.5 mm showed a greater effect on Dr than those with larger diameters. Compared to cropland, the nine restored types reduced K r by 76.26% to 94.26% and improved τ c by 1.51 to 4.68 times. The decrease in K r and the increase in τ c were significantly affected by organic matter content, water‐stable aggregate, mean weight diameter of aggregate and root mass density. The combination of grass species ( Cleistogenes caespitosa ) and shrub ( Hippophae rhamnoides ) could be considered the best vegetation restoration types for improving soil resistance of gully heads to concentrated flow. © 2019 John Wiley & Sons, Ltd. Abstract : Revegetation reduces soildetachment and soil erodibility of gully heads by 77.11%‐95.81% and76.26%‐94.26%, respectively, but improves critical shear stress by 1.51‐4.68times. The combination of Cleistogenes caespitosa and Hippophae rhamnoidesshould be preferred for controlling soil erosion of gully heads.